Tourism development strategy in Jember Regency: Islamic economic perspective - Ilham, Muhammad; Shioleh, Chotir Mochammad; Maghribi, Moch. Maulana; Siswanto, Adil (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to analyze the development of the tourism sector in Jember Regency through a Sharia economic perspective, addressing the challenges hindering optimal growth despite the region's rich potential in religious, cultural, and natural tourism. The research identifies key issues in current tourism management and explores how Islamic economic principles can contribute to sustainable and inclusive development. The significance lies in integrating Sharia-compliant strategies into regional tourism planning, offering an alternative model for economic empowerment in predominantly Muslim regions. Method: A qualitative descriptive approach is employed, supported by SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to evaluate internal and external factors affecting tourism development in Jember Regency. Data were collected through field observations, interviews with local stakeholders, and document reviews. The analytical framework integrates Sharia economic principles with strategic planning tools to assess viable pathways for halal tourism development. Practical Applications: The findings provide actionable strategies for policymakers and local communities, including the promotion of halal tourism, empowerment of Sharia-based micro, small, and medium enterprises (MSMEs), improvement of tourism infrastructure, digitalization of promotional efforts, and utilization of Sharia finance for investment. These measures are expected to enhance tourism competitiveness while fostering inclusive economic growth aligned with Islamic values. Conclusion: The study concludes that integrating Sharia economic principles into tourism development offers a sustainable and ethically grounded approach to regional progress in Jember Regency. By leveraging its unique potentials through halal tourism and Islamic financial mechanisms, the region can achieve not only economic resilience but also social inclusivity, contributing to a broader understanding of faith-based sustainable development in Indonesia’s local economies.